Bethesda Assay for Detecting Inhibitory Anti-ADAMTS13 Antibodies in Immune-Mediated Thrombotic Thrombocytopenic Purpura - Vendramin, Chiara; Thomas, Mari; Westwood, John-Paul; Scully, Marie (TH Open, 2018)
A diagnosis of thrombotic thrombocytopenic purpura (TTP) is confirmed by a severe deficiency (<10%) of a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13 (ADAMTS13) activity. Autoantibodies to ADAMTS13 can be detected with a simplified enzyme-linked immunosorbent assay (ELISA). An alternative methodology is a Bethesda assay, which has never been formally assessed in TTP. This study aimed to investigate the inhibitory anti-ADAMTS13 antibody assay and determine if the Bethesda assay is advantageous compared with the ELISA, measuring total immunoglobulin G (IgG) antibodies to ADAMTS 13. The Bethesda method determines the neutralizing activity of anti-ADAMTS13 antibodies in pooled normal plasma. We selected six immune-mediated TTP (iTTP) patients with ADAMTS13 activity levels <10% and strong ADAMTS13 inhibitors by 50:50 mixing studies and analyzed anti-ADAMTS13 antibodies using the Bethesda and ELISA assays. ADAMTS13 activity was stable at room temperature, while a time-dependent decrease in activity was detected in assay conditions of 37°C. Adding 5 mM Ca2+ to citrated plasma prevented loss of ADAMTS13 activity with time. There was time dependence to the antibody-mediated inactivation, after 2-hour incubation. Two of the iTTP patients had no detectable ADAMTS13 antibodies by the Bethesda assay, but had high titer of anti-ADAMTS13 antibodies and low ADAMTS13 antigen levels. The Bethesda assay can only detect anti-ADAMTS13 antibodies that functionally inhibit ADAMTS13. The anti-ADAMTS13 IgG ELISA instead allows the rapid identification of total IgG autoantibodies, detecting both inhibitory and noninhibitory antibodies.
Keywords: ADAMTS13 protein; Human plasma; anti-ADAMTS13 inhibitors; Bethesda assay; enzyme-linked immunosorbent assay; thrombotic thrombocytopenic purpura